2011
DOI: 10.1111/j.1537-2995.2011.03130.x
|View full text |Cite
|
Sign up to set email alerts
|

The appropriateness of red blood cell use and the extent of overtransfusion: right decision? Right amount?

Abstract: BACKGROUND:Shrinkage of the donor pool coupled with an increasing demand for blood presents a major challenge to maintaining an adequate blood supply. Consequently it has become even more important to reduce inappropriate blood use, including decisions about when and how much blood to prescribe. This study aimed to ascertain the levels of inappropriate practice and factors associated with it. STUDY DESIGN AND METHODS:The medical records of a randomly selected sample of hospital patients in Northern Ireland who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 25 publications
4
50
3
1
Order By: Relevance
“…Number of cases of overtransfusion in this subgroup was 10 (13%), when overtransfusion was defined as post transfusion Hb of 1.2 mmol/L higher than the threshold set for that group of patients. 6 In most inpatient transfusion episodes, it was not possible to determine the charge of the person making the primary transfusion decision, since decisions were made in a team of junior and senior doctors. All transfusion decisions in the outpatient clinic were made by or supervised by a senior specialist.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Number of cases of overtransfusion in this subgroup was 10 (13%), when overtransfusion was defined as post transfusion Hb of 1.2 mmol/L higher than the threshold set for that group of patients. 6 In most inpatient transfusion episodes, it was not possible to determine the charge of the person making the primary transfusion decision, since decisions were made in a team of junior and senior doctors. All transfusion decisions in the outpatient clinic were made by or supervised by a senior specialist.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have shown that overtransfusion is frequent 6 when the level of post transfusion hemoglobin (Hb) is compared to current guidelines. 3 This seems to be one of the reasons for the high transfusion rate in Denmark, and our hypothesis was…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, substantial variability in transfusion practice persists [2]. It is important to identify contemporary variability, and which patient, provider, and institutional factors drive this variability.…”
Section: Introductionmentioning
confidence: 99%
“…Although small in absolute terms, this is high relative to other high-resource countries. 3 Wide variation in transfusion rates [4][5][6][7][8] is evident, including between hospitals. 3 Studies reporting transfusion practices outside of obstetrics frequently report a preference for at least 2 units when blood is transfused.…”
mentioning
confidence: 98%
“…3 Studies reporting transfusion practices outside of obstetrics frequently report a preference for at least 2 units when blood is transfused. 4,9,10 In nonobstetric patients, liberal blood transfusion has been associated with higher morbidity (cardiac, renal, and neurologic events and higher infection rates) and increased mortality compared with patients who received more restrictive transfusion. 7,8,11 Other transfusion risks include receiving the wrong blood, transfusion-transmitted infection, immunomodulation, 11 and red cell alloimmunization.…”
mentioning
confidence: 99%